2015
DOI: 10.1007/s10971-015-3664-x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in electrical properties of sol–gel-derived In-doped ZnO thin film by electron beam treatment

Abstract: In-doped ZnO thin films were prepared by a sol-gel spin coating method. Since several issues with In doping have been reported, such as degradation of crystallinity and deterioration of electrical resistivity at high Indoping levels, co-doping with Ga and electron beam treatment was demonstrated in this study. When In dopant was added to the ZnO thin film at 0.5 mol%, it increased the carrier concentration, thereby reducing the resistivity of the film. In contrast, further doping by Ga in the presence of In di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The higher the In-doping concentration, the smaller the E g is. Other groups also found that the E g decreased with the increase of the In-doping concentration. With the increase of the In-doping concentration, the hybridization level of the s orbitals between In and ZnO conduction band becomes stronger, and consequently results in the decrease of the band gap. , …”
Section: Resultsmentioning
confidence: 96%
“…The higher the In-doping concentration, the smaller the E g is. Other groups also found that the E g decreased with the increase of the In-doping concentration. With the increase of the In-doping concentration, the hybridization level of the s orbitals between In and ZnO conduction band becomes stronger, and consequently results in the decrease of the band gap. , …”
Section: Resultsmentioning
confidence: 96%
“…The incorporation of indium into ZnONPs allows the inhibition of the recombination of photo-generated electron and holes, thus collecting more charges and enhancing the conversion efficiency values. [25] Kim et al [26] synthesized the In-doped ZnO materials via the sol-gel route. They found that when indium dopant was added to ZnO material at 0.5 mol%, it increased the carrier concentration, therefore reducing the resistivity of the materials.…”
Section: Introductionmentioning
confidence: 99%